Indigenous chicken in Ethiopia: Genetic potential and attempts made at improvement - Dessie, Tadelle; Yami, A.; Peters, Kurt J. (Informa UK Limited, 2000)
This paper describes the rural poultry production system and the role of scavenging chicken in rural household economy of Ethiopia. Past attempts that have been made to improve the production and productivity of local birds through upgrading (distribution of exotic birds) and crossbreeding in Ethiopia are assessed. The merits and demerits of the different ecotypes of indigenous chicken and their crosses are reviewed. The significance of indigenous birds in the face of extensive importation of exotic birds are assessed. Finally, future areas of research on indigenous chicken is recommended to aid the development of rational utilisation of the local chicken genetic resource.